2015
DOI: 10.11648/j.ajns.20150404.18
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Experiences of Kangaroo Mother Care During Hospitalization of Their Preterm Babies at an Academic Hospital in Johannesburg

Abstract: Kangaroo mother care (KMC) implies placing the newborn pre-term baby in intimate skin-to-skin contact with the mother's chest and abdomen coupled with frequent and preferably exclusive breast-feeding. This is similar to marsupial care-giving, where the premature baby is kept warm in the maternal pouch and close to the breasts for unlimited feeding. KMC has emerged as a non-conventional low cost method for newborn care that provides warmth, touch, and security to the newborn and is believed to confer significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
1
3
0
6
Order By: Relevance
“…The mothers in the ward found KMC useful because it allowed them to be closer to their babies and to be more attuned to their babies. This was similar to findings from another South African study in Johannesburg where the mothers also reported KMC to be satisfactory, as they felt closer to their babies and could monitor their growth closely (Kipchumba Tarus, 2015). KMC was accepted by the mothers and seen to be a beneficial concept that had some parallels to the Xhosa women’s own culture.…”
Section: Discussionsupporting
confidence: 88%
“…The mothers in the ward found KMC useful because it allowed them to be closer to their babies and to be more attuned to their babies. This was similar to findings from another South African study in Johannesburg where the mothers also reported KMC to be satisfactory, as they felt closer to their babies and could monitor their growth closely (Kipchumba Tarus, 2015). KMC was accepted by the mothers and seen to be a beneficial concept that had some parallels to the Xhosa women’s own culture.…”
Section: Discussionsupporting
confidence: 88%
“…Other studies on the scale-up of KMC have previously described challenges, including that mothers may get tired of being in one position for prolonged periods [ 7 , 9 , 20 ] resulting in sleep deprivation for the mother [ 21 , 22 ]. However, to the best of our knowledge, this is the first study investigating mothers’ QoL while delivering KMC in a resource-limited setting.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the form of KMC practiced may have implications. While intermittent KMC was associated with improved maternal mental health [ 33 ], continuous KMC was exhausting and stressful for caregivers to undertake the care of vulnerable low birthweight infants full-time [ 21 , 22 ]. KMC wards at our study hospitals in Malawi were not equipped with incubators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A rotina diária de demandas geradas para a mãe pelos cuidados ao bebê, o distanciamento da vivência domiciliar e a longa permanência no ambiente hospitalar torna o período de hospitalização do bebê por vezes estressante, o que culmina tanto no desgaste físico como emocional da mãe (25)(26) .…”
Section: Discussionunclassified